Room-Temperature Voltage Stressing Effects on Resistive Switching of Conductive-Bridging RAM Cells with Cu-Doped SiO2 Films - Jian-Yang Lin; Bing-Xun Wang (Advances in Materials Science and Engineering)
SiO2 or Cu-doped SiO2 (Cu:SiO2) insulating films combined with Cu or W upper electrodes were constructed on the W/Si substrates to form the conductive-bridging RAM (CB-RAM) cells. The CB-RAMs were then subjected to a constant-voltage stressing (CVS) at room temperature. The experimental results show that the room-temperature CVS treatment can effectively affect the current conduction behavior and stabilize the resistive switching of the memory cells. After the CVS, the current conduction mechanisms in the high resistance state during the set process of the Cu/Cu:SiO2/W cell can be changed from Ohm’s law and the space charge limited conduction to Ohm’s law, the Schottky emission, and the space charge limited conduction. Presumably, it is due to the breakage of the conduction filaments during the CVS treatment that the conduction electrons cannot go back to the back electrode smoothly.